Penerapan Manajemen Strategi dalam Peningkatan Mutu MAS Robithotul Istiqamah Kecamatan Huristak Kabupaten Padang Lawas - Asmaria Hsb; Asma Yulina; Sukriani Hasibuan (FONDATIA, 2022)
This study aims to describe the targets of strategic management at MAS Robithotul Istiqamah, to know the factors in learning progress, and the implementation of strategic management at MAS Robithotul Istiqamah, Kec. Huristak, Kab. Old Field. This study uses library research, data collection methods through online-based interview methods, namely by using the Whatsapp application. The findings that the researchers have found are: 1) that the strategic management targets at MAS Robithotul Istiqamah support projects and instructive exercises in encouraging learning progress. 2) the learning progress factors at MAS Robithotul Istiqamah have been in accordance with the vision and mission set by the school. 3) the implementation of strategic management at MAS Robithotul Istiqamah can help the completion of the learning system in schools.